Penentuan Jumlah Produksi Ayudes menggunakan Fuzzy Tsukamoto - Lusye Bakarbessy; Doms Upuy; Arlene Henny Hiariey (JURNAL SAINTIKA UNPAM, 2023)
CV Abadi Tiga Mandiri Ambon as one of the companies producing goods in the form of 'Ayudes' branded drinking water in the city of Ambon. The production of bottled water that the company has been doing so far depends on the number of existing requests. However, with an uncertain number of requests each month, it is difficult for the company to determine the amount of production that should be produced. This study aims to predict the amount of bottled water production to meet consumer demand using the Fuzzy Tsukamoto Method. The results of the study using the Tsukamoto Fuzzy Method using the "And" and "Or" operators obtained the amount of ayudes production greater than demand and supply. This can be seen when the demand for 175000 cartons and the existing supply of 6000 cartons using the Tsukamoto fuzzy resulted in 182000 cartons that had to be produced